Determinants of child wasting in Bhutan. Insights from nationally representative data - Aguayo, Víctor M; Badgaiyan, Nina; Dzed, Laigden (Public health nutrition, 2017)
To characterize the epidemiology of wasting and identify the main predictors of wasting, severe wasting and poor weight-for-height in children. We analysed a nationally representative sample of 2028 children (Multiple Indicator Survey, 2010). Royal Kingdom of Bhutan. Children aged 0-23 months. Wasting prevalence was significantly higher among infants aged 0-11 months than among children aged 12-23 months (12·0 v. 6·7 %; P=0·004) and among boys than girls (11·0 v. 7·5 %; P=0·04). Children from the Western region had 63 % higher odds of being wasted than children from the Central/Eastern regions (adjusted OR (AOR)=1·63; 95 % CI 1·14, 2·34). Poor feeding practices were among the most significant predictors of wasting and severe wasting. Children who were given prelacteal feeds in the first days of life had 2·5 times higher odds of being severely wasted than those who were not (AOR=2·49; 95 % CI 1·19, 5·19); inadequate complementary feeding in children aged 0-23 months was associated with 58 % higher odds of being wasted (AOR=1·58; 95 % CI 1·02, 2·47) and 2·3 times higher odds of being severely wasted (AOR=2·28; 95 % CI 1·13, 4·58). The association of poor infant feeding practices with wasting and severe wasting was particularly significant in infants (0-11 months). Programmes for the detection and treatment of severely wasted children need to prioritize very young children (0-11 months), particularly in the Western region. Programmes for the prevention of wasting need to prioritize the improvement of complementary foods and feeding practices in children aged 6-23 months.